2020
DOI: 10.1177/1077559520930819
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Associations With Parents’ Child Abuse Risk and At-Risk Parenting: A Multimethod Longitudinal Examination

Abstract: The current investigation considered salivary testosterone as a potential biomarker of physical child abuse risk. Parents enrolled in a prospective, longitudinal, multimethod study beginning prenatally provided saliva when their toddlers were 18 months old. Mothers and fathers self-reported on their empathy, frustration tolerance, and child abuse risk, as well as completing analog tasks of frustration intolerance and child abuse risk and participating in structured parent-child interactions. In contrast to mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
4
0
1
Order By: Relevance
“…The few studies that examined associations between T and maternal caregiving behavior indicated mixed results. While higher T was associated with more sensitivity in one study (Endendijk et al, 2016), and lower maternal engagement in another study (Clowtis et al, 2016), T was not predictive of maternal behavior in other studies (Bos et al, 2018;Gordon et al, 2017;Rodriguez et al, 2020). It thus remains unclear whether and how T is related to maternal caregiving quality.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The few studies that examined associations between T and maternal caregiving behavior indicated mixed results. While higher T was associated with more sensitivity in one study (Endendijk et al, 2016), and lower maternal engagement in another study (Clowtis et al, 2016), T was not predictive of maternal behavior in other studies (Bos et al, 2018;Gordon et al, 2017;Rodriguez et al, 2020). It thus remains unclear whether and how T is related to maternal caregiving quality.…”
mentioning
confidence: 95%
“…For these three research questions, and following the dualhormone hypothesis, we hypothesized that higher CORT and T would predict lower paternal caregiving quality in toddlerhood, and that the negative association between T and caregiving quality would be stronger for fathers with lower CORT. Given that studies find both positive and negative associations between CORT, T and maternal caregiving behavior (Endendijk et al, 2016;Clowtis et al, 2016;Finegood et al, 2016;Mills-Koonce et al, 2009;Thompson and Trevathan, 2008), while other studies do not find any associations (Bos et al, 2018;Gordon et al, 2017;Rodriguez et al, 2020), we did not set up specific hypotheses on the direction of the associations between T, CORT and maternal caregiving quality in toddlerhood.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…9 Terlepas dari hormon testosteron, terjadinya kejahatan seksual merupakan interaksi kompleks antara fungsi kognitif, emosional, sosio-ekonomi, dan kontekstual seseorang. 9,10 Saat ini, tindakan kastrasi kimia yang bertujuan untuk menurunkan impuls seksual pelaku cukup banyak diterapkan. Beberapa negara bagian di Amerika Serikat dan sejumlah negara di Benua Eropa serta Asia sudah menggunakan metode ini selama beberapa tahun terakhir sebagai bagian dari rehabilitasi pelaku.…”
Section: Testosteron Dan Kejahatan Seksualunclassified
“…SES was measured by averaging standardized income and education variables (e.g., Pu & Rodriguez, 2021;Rodriguez et al, 2021;Gardner et al, 2017). Education was reported on a 5-point scale, ranging from (1) Less than a high school diploma to (5) Graduate school.…”
Section: Socioeconomic Statusmentioning
confidence: 99%